Durable Control of Mycosis Fungoides after Sepsis: "Coley's Toxin?" Case Report and Review of the Literature. (4th August 2019) - Heyman, Benjamin; Kelsey, Chris R.; Beaven, Anne
Abstract : Mycosis fungoides, along with Sezary syndrome, is the most common subtype of cutaneous T-cell lymphoma. In this report, we present a patient with advanced-stage mycosis fungoides, who after successful treatment of methicillin-resistant Staphylococcus aureus bacteremia had prolonged disease control off systemic therapy. While this may have been due to single-agent gemcitabine, which can result in long remission, we hypothesize that our patient's durable response was in part due to the immune response elicited after treatment of her severe infection.